A NEW SLIP-LINE FIELD MODELING OF ORTHOGONAL MACHINING WITH A ROUNDED-EDGE WORN CUTTING TOOL - Uysal, Alper; Altan, Erhan (TAYLOR & FRANCIS INC, 2014)
In this study, a new slip-line field model and its associated hodograph for orthogonal cutting with a rounded-edge worn cutting tool are developed using Dewhurst and Collins's matrix technique. The new model considers the existence of dead metal zone in front of the rounded-edge worn cutting tool. The ploughing force and friction force occurred due to flank wear land, chip up-curl radius, chip thickness, primary shear zone thickness and length of bottom side of the dead metal zone are obtained by solving the model depending on the experimental resultant force data. The effects of flank wear rate, cutting edge radius, uncut chip thickness, cutting speed and rake angle on these outputs are specified.
Keywords: dead metal zone; friction force; ploughing force; rounded-edge worn cutting tool; slip-line field model; SECONDARY RAKE FACE; ADHESION FRICTION; CHIP CONTACT; PART II; ROUNDNESS; INTERFACE; STRAIN; FLANK; Engineering; Materials Science